The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1371/journal.pone.0228138
|View full text |Cite
|
Sign up to set email alerts
|

The effect of enrofloxacin on enteric Escherichia coli: Fitting a mathematical model to in vivo data

Abstract: Antimicrobial drugs administered systemically may cause the emergence and dissemination of antimicrobial resistance among enteric bacteria. To develop logical, research-based recommendations for food animal veterinarians, we must understand how to maximize antimicrobial drug efficacy while minimizing risk of antimicrobial resistance. Our objective is to evaluate the effect of two approved dosing regimens of enrofloxacin (a single high dose or three low doses) on Escherichia coli in cattle. We look specifically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
(43 reference statements)
1
9
0
Order By: Relevance
“…Enrofloxacin was amongst the most frequently reported prescribed antibiotics in this study; over a third (38.5%) of the respondents reported prescribing enrofloxacin in animals. Fluoroquinolones are categorised as critically important antimicrobials (CIAs) for human health (Erwin et al 2020 ; WHO 2019 ), and there is concern that the use of enrofloxacin in animals could lead to sharing of genes encoding resistance to fluoroquinolones in people. Veterinarians can play a role in protecting CIAs (Wood 2018 ) such as enrofloxacin by using these as ‘last resort’ antimicrobials.…”
Section: Discussionmentioning
confidence: 99%
“…Enrofloxacin was amongst the most frequently reported prescribed antibiotics in this study; over a third (38.5%) of the respondents reported prescribing enrofloxacin in animals. Fluoroquinolones are categorised as critically important antimicrobials (CIAs) for human health (Erwin et al 2020 ; WHO 2019 ), and there is concern that the use of enrofloxacin in animals could lead to sharing of genes encoding resistance to fluoroquinolones in people. Veterinarians can play a role in protecting CIAs (Wood 2018 ) such as enrofloxacin by using these as ‘last resort’ antimicrobials.…”
Section: Discussionmentioning
confidence: 99%
“…Fluoroquinolone antibiotics such as danofloxacin and enrofloxacin are approved in the US for use in cattle and swine, but their extra-label use has been prohibited by the FDA 11 , 12 . They are effective in clearing susceptible respiratory infections in animals, but they can pass from the general circulation and be accumulated in the intestinal lumen 12 14 . The elimination mechanisms of FQs involve renal and hepatic pathways, with the biliary excretion contributing to the accumulation in the intestine 2 , 15 .…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been shown in pigs that enrofloxacin reached the concentration level that could reduce E. coli population in the intestinal lumen after being administered to two groups of pigs orally and parenterally alike 13 . Altogether, previous studies indicate that the FQ elimination mechanisms can result in the deposition of FQs in the intestinal content to the concentration level that can alter microbial diversity and induce selective pressure, leading to the emergence and spread of antimicrobial resistance (AMR) 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, enrofloxacin can disrupt the gut commensal bacteria, even when treatment is by intramuscular injection [ 90 ]. Enrofloxacin can influence the population dynamics of enteric bacteria and may select for resistance [ 91 ]. Besides, it has been observed that intramuscular enrofloxacin treatment reduces the faecal E. coli wild type population [ 34 , 92 ], and some authors have observed that at the end of enrofloxacin treatment only non-wild type E. coli isolates are found in faeces [ 34 ].…”
Section: Discussionmentioning
confidence: 99%